2017
DOI: 10.1016/j.chieco.2017.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Does wage justice hamper creativity? Pay gap and firm innovation in China

Abstract: Although the pay gap between executives and employees has received considerable attention, its economic consequences remain unclear due to the unavailability of data. In this study, we examine the effects of the pay gap on firm innovation by using data from Chinese listed firms. We show that: 1) the first-order effect of pay gap on firm innovation is significantly positive, supporting the tournament theory; 2) however, when pay gap is relatively high, the importance of comparison theories increases; 3) high ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(28 citation statements)
references
References 47 publications
1
27
0
Order By: Relevance
“…ChunLiu, Liang Sun [46], Quanxiong Zhou and Weiping Zhu [47] have all found that the salary gap of state-owned enterprises is positively related to enterprise performance. Some empirical studies have also proved that the salary gap is conducive to enterprise innovation [48], which supports the tournament theory. There are also some empirical studies find that the internal salary gap of enterprises have a negative impact on the company's product quality [49] and enterprise market performance [50] through power and earnings management [11] [51] [52] etc.…”
Section: Executive-employee Pay Gapsupporting
confidence: 59%
“…ChunLiu, Liang Sun [46], Quanxiong Zhou and Weiping Zhu [47] have all found that the salary gap of state-owned enterprises is positively related to enterprise performance. Some empirical studies have also proved that the salary gap is conducive to enterprise innovation [48], which supports the tournament theory. There are also some empirical studies find that the internal salary gap of enterprises have a negative impact on the company's product quality [49] and enterprise market performance [50] through power and earnings management [11] [51] [52] etc.…”
Section: Executive-employee Pay Gapsupporting
confidence: 59%
“…Apart from the implementation of VAT reform, export performance can be affected by the intrinsic characteristics and financial condition of firms. Therefore, we introduce a vector of variables at the firm level to control for the above‐mentioned impacts following the studies on firms’ behavior and performance (Alfaro et al., 2019a; Geng et al, 2018; Xu et al., 2017). In particular, we include firm size, profitability, and leverage as the control variables in the model.…”
Section: Empirical Frameworkmentioning
confidence: 99%
“…Feldman and Florida [ 37 ] reported a high correlation between innovation and patents, reaching 0.934. In this study, we used patents to measure innovation—a popular approach also used in some recent studies [ 30 , 32 , 38 – 41 ]. In addition, patents represent the successful resource integration and team cooperation, which are successful innovation, and R&D expenditure could be uneconomical [ 42 , 43 ].…”
Section: Data and Modelingmentioning
confidence: 99%